Estructuración de un método para la detección de glaucoma mediante reconocimiento de imágenes usando inteligencia artificial (2019)
This work shows how ophthalmologists diagnose whether or not a patient has glaucoma using non-invasive biomedical equipment that provides useful information in this regard. A list of the advantages and disadvantages offered by each of the ophthalmological techniques found was made, where finally, the taking of fundus photographs was chosen as the examination with the greatest number of virtues according to the objective of this project.